Border Effects Without Borders: What Divides Japan's Internal Trade? - Jens Wrona (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper identifies a “border” effect in the absence of a border. The finding that trade between East- and West-Japan is 23.1 to 51.3 percent lower than trade within both country parts, is established despite the absence of an obvious east-west division due to historical borders, cultural differences or past civil wars. Post-war agglomeration processes, reflected by the contemporaneous structure of Japan's business and social networks, rather than cultural differences, induced by long-lasting historical shocks, are identified as an explanation for the east-west bias in intra-Japanese trade.
Keywords: F14; F15; F12; 330; border effects; gravity equation; intra-national Trade; Japan